A Mechanistic Understanding of Nonclassical Crystal Growth in Hydrothermally Synthesized Sodium Yttrium Fluoride Nanowires - Bard, Alexander B.; Zhou, Xuezhe; Xia, Xiaojing; Zhu, Guomin; Lim, Matthew B.; Kim, Seung Min; Johnson, Matthew C.; Kollman, Justin M.; Marcus, Matthew A.; Spurgeon, Steven R.; Perea, Daniel E.; Devaraj, Arun; et al. (AMER CHEMICAL SOC, 2020)
Sodium yttrium fluoride (NaYF4) is an important upconverting material with many potential uses in chemistry, materials science, and biology, which can be synthesized hydrothermally in both cubic (alpha) and hexagonal (beta) crystallo-graphic polymorphs. Understanding the mechanisms underlying the phase conversion between the cubic and hexagonal polymorphs is of great interest to help inform future synthetic efforts, for example in the design of atomically precise quantum materials with well-defined sizes and morphologies. In this work, we use a combination of analytical transmission electron microscopy (TEM), scanning transmission electron microscopy (STEM), powder X-ray diffraction (XRD), in situ liquid cell TEM, atom probe tomography (APT), and extended X-ray absorption fine structure (EXAFS) measurements to show that the hexagonal NaYF4 nanowires form through a nonclassical crystal growth mechanism involving the formation and subsequent oriented attachment of mesocrystals consisting of cubic (alpha) phase units. EXAFS measurements also suggest that substitutional Yb3+ point defects within NaYF4 are distributed evenly throughout the crystal lattice without clustering and also that they may exhibit selective substitution into one of the two possible trivalent yttrium sites in the unit cell for hydrothermally synthesized beta-NaYF4.
Keywords: AMORPHOUS CALCIUM-CARBONATE; RARE-EARTH FLUORIDES; ORIENTED ATTACHMENT; UPCONVERTING NANOPARTICLES; LASER REFRIGERATION; SOLAR-CELLS; CONVERSION; TRANSFORMATION; NANOCRYSTALS; LUMINESCENCE